Synthesis of nonracemic hydroxyglutamic acids - Piotrowska, Dorota G.; Głowacka, Iwona E.; Wróblewski, Andrzej E.; Lubowiecka, Liwia (Beilstein Journal of Organic Chemistry, 2019)
Glutamic acid is involved in several cellular processes though its role as the neurotransmitter is best recognized. For detailed studies of interactions with receptors a number of structural analogues of glutamic acid are required to map their active sides. This review article summarizes syntheses of nonracemic hydroxyglutamic acid analogues equipped with functional groups capable for the formation of additional hydrogen bonds, both as donors and acceptors. The majority of synthetic strategies starts from natural products and relies on application of chirons having the required configuration at the carbon atom bonded to nitrogen (e.g., serine, glutamic and pyroglutamic acids, proline and 4-hydroxyproline). Since various hydroxyglutamic acids were identified as components of complex natural products, syntheses of orthogonally protected derivatives of hydroxyglutamic acids are also covered.
Keywords: amino acids; asymmetric synthesis; chiral catalysis; chiral pool; glutamate analogues